Capital structure, firm performance and ownership: evidence from commercial banking industry in Taiwan - Kuo, Tai-Yun (2018)
This study investigates the performance of commercial banks in Taiwan during 2013 to 2017. Through employ quantitative method to compare the performance of public, domestic private and foreign banks, and to find out the relationship between performance and firm’s abilities in the Taiwanese commercial banking industry. In the performance comparison, employ Analysis of Variance (ANOVA) of financial ratios to compare the bank capability of profitability (return on assets, return on equity), liquidity (debt to equity), efficiency (net interest margin, cost to income ratio) and growth (assets, loans, deposits growth) between the three categories of banks. In bank’s performance analysis, use multiple regression analysis to find out the effect of bank’s profitability, liquidity, efficiency and growth on the performance outcome.